Effect of laparoscopic ovarian drilling on serum anti-Mullerian hormone in clomiphene citrate resistant polycystic ovarian syndrome patients - Shankar, Ambika; Nagar, Oby; ., Shakuntla; Meghwal, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: PCOS (polycystic ovarian syndrome) is the most common cause of anovulatory infertility, the purpose of our study was to see the effect of laparoscopic ovarian drilling on the ovarian reserve (with AMH as an indicator of ovarian reserve) and its safety as 2nd line of treatment in patients resistant to clomiphene citrate. Methods: This was a prospective interventional study conducted on 40 clomiphene citrate resistant PCOS women attending the infertility OPD. This study was conducted over a period of 1 year May 2019 to May 2020. Laparoscopic ovarian drilling (LOD) was done and these subjects were studied preoperatively and postoperatively on day 7 and day 30 for change in AMH (anti-Mullerian hormone) levels. Results: There is a significant change in the AMH level post LOD day 7 and 30 but not so severe that it will lead to premature ovarian failure. The amount of drop in AMH (day 30) increases till 20 ng/ml beyond which it shows a decrease. Conclusions: If LOD is done in a proper manner in women with sufficient ovarian reserve (high AMH), it will not adversely affect the ovarian reserve (the fall is not enough to cause premature ovarian insufficiency).